Mechanical properties optimization of Si3N4 ceramics by in-situ introduction of core-shell structural W-Fe5Si3. (1st September 2020) - Wang, Lujie; Qi, Qian; Yang, Xiao; Zhang, Hui; Liu, Zehua; Ge, Sheng; Peng, Xinglin; Liu, Leimin; Liu, Yan; Liu, Xuejian; Huang, Zhengren; Jiang, Dongliang
Abstract: It is one inevitable problem that optimizing properties of Si3 N4 ceramics by introducing second phase would produce thermal mismatch stress, which may lead to interfacial bonding and strength deterioration. In this work, a novel strategy for regulating the residual thermal stress and inhibiting the interfacial debonding in Fe5 Si3 /Si3 N4 ceramics was proposed, which results in the simultaneous increase of strength and toughness of Si3 N4 ceramics. Instead of Fe5 Si3 particle, the core-shell structural W-Fe5 Si3 particles were in situ generated in the Si3 N4 matrix by introducing a new WSi2 /FeSi2 powder directly. The maximum principal stress, residual radial and tangential stress around the core-shell structural W-Fe5 Si3 and Fe5 Si3 particle were compared by using the finite element method. The W core inhibits the radial contraction of the Fe5 Si3 shell during the cooling process and alters the residual thermal stress distribution. Both the Griffith fracture equation and Lange's energy model indicate that the core-shell structural W-Fe5 Si3 inhibits the interfacial debonding, which is consistent with the experiment result. As a result, with the increase of WSi2 /FeSi2 addition from 0 to 1 wt%, the fracture toughness of Si3 N4 ceramics increases from 7.1 to 7.7 MPa m 1/2, and the strength improves from 1016 to 1173 MPa.